Impact of silicone midline catheter tip location on catheter-related complications and indwelling duration: results from a multicentre randomised clinical trial in China - Hong Sun; Lei Wang; Shengxiao Nie; Shengmiao Ma (BMJ Open)
Objective To explore the impact of the terminal tip location of silicone midline catheter (MC, a type of intravenous catheter measuring 20–30 cm in length and inserted into upper arm veins using a modified Seldinger technique) in the subclavian vein group versus axillary vein group on catheter-related complications and indwelling duration.Design This is a randomised controlled study.Setting Twenty-seven tertiary hospitals in China.Participants Between September 2022 and October 2023, 2307 patients underwent MC placement and were randomly assigned to either the axillary vein group (n=1124) or the subclavian vein group (n=1183).Outcome measures There were two outcome measures: one was to compare the incidence of catheter-related complications (eg, catheter-related thrombosis, infection, catheter occlusion, etc.) between the two groups, and the other was to compare the indwelling duration between the groups.Results The total observed incidence of catheter-related complications in the axillary vein group and subclavian vein group was 1.0% (11/1124) and 0.8% (10/1183), respectively. There was no statistically significant difference in the total incidence of catheter-related complications. The median indwelling duration (median (IQR)) of the two groups was 10 days (7, 15) and 10 days (7, 15), respectively. The two groups had no statistical difference in the indwelling duration.Conclusions Our findings suggested that the terminal tip of silicone MC in the subclavian vein would not increase the incidence of catheter-related complications. Silicone MC was a safe catheter for the low incidence of catheter-related complications and could be popularised in clinical practice.Trial registration number ChiCTR2200058942; Chinese Clinical Trial Registry.